On the Occurrence of Lions in the Greek and Roman World - Fögen, Thorsten (Polskie Towarzystwo Filologiczne, 2023)
This article focuses on descriptions of the geographical occurrence of lions in Greek and Latin literature. Special attention is devoted to Homer, Herodotus, Xenophon, Aristotle, Pausanias, Pliny the Elder, Aelian, Livy, Martial and Statius. Through close reading, this contribution examines in what contexts lions are portrayed and for what purpose. Aspects of literary genre and readership are also taken into account. Apart from the cultural and symbolic value of lions for the Greek and Roman world, information is extrapolated on the different types of interactions between lions and humans, on the keeping of lions, and on zoogeographical aspects. The use of these animals in the circus and for games is also investigated briefly.